Bethe Ansatz for the Ruijsenaars Model of BC₁-Type - Chalykh, O. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We consider one-dimensional elliptic Ruijsenaars model of type BC₁. It is given by a three-term difference Schrödinger operator L containing 8 coupling constants. We show that when all coupling constants are integers, L has meromorphic eigenfunctions expressed by a variant of Bethe ansatz. This result generalizes the Bethe ansatz formulas known in the A₁-case.